Strong magnetic powder composition

The ferromagnetic powder composition with a tailored coating structure addresses high-frequency performance issues by enhancing resistivity and reducing core losses, resulting in efficient soft magnetic components for power electronics.

JP7621443B2Active Publication Date: 2025-01-24HOGANAS AB
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2023180717
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2018-05-30
Filing Date
2023-10-20
Publication Date
2025-01-24
Estimated Expiration
2039-05-28

AI Technical Summary

Technical Problem

Existing soft magnetic materials face challenges in maintaining high resistivity and low core losses, especially at high frequencies, leading to increased eddy current and hysteresis losses, which affect their efficiency and performance in power electronics applications.

Method used

A ferromagnetic powder composition with a specific coating structure, comprising iron-based cores coated with phosphorus-containing insulating layers and additional layers formed from compounds of the formula (I), allowing for high resistivity and low core losses, and a manufacturing process involving compression and heat treatment without organic binders.

Benefits of technology

The composition achieves high saturation magnetic flux density, low core losses, and improved mechanical strength, enabling efficient operation in power electronics components like inductors and reactors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007621443000003
    Figure 0007621443000003
  • Figure 0007621443000004
    Figure 0007621443000004
  • Figure 0007621443000005
    Figure 0007621443000005
Patent Text Reader

Abstract

To provide powder core for use at frequencies above 2 kHz, 5-100 kHz where high resistivity and low iron losses are essential, an electrical insulation iron-based soft magnetic powder composition, a soft magnetic composite component obtained from the powder composition, and a manufacturing process thereof.SOLUTION: In a composition including particles A and particles B, the core of the particle A is a soft magnetic iron core, the core of the particle B is formed from an Fe-Si alloy, the surfaces of the respective cores of the particles A and B are coated with phosphorus-containing insulating layers A1 and B1, respectively, and the particle A with an insulating coating layer A1 is provided with an additional layer A2 on the top of the layer A1.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an electrically insulating iron-based soft magnetic powder composition, a soft magnetic composite part obtained from the powder composition, and a process for its manufacture. In particular, the present invention relates to a soft magnetic powder composition for the manufacture of a soft magnetic part operating at high frequencies, the part being suitable for use, for example, as an inductor or reactor for power electronics. [Background technology]

[0002] Soft magnetic materials are used in applications such as cores for inductors, stators and rotors for electric machines, actuators, sensors and transformer cores. Traditionally, soft magnetic cores, such as rotors and stators for electric machines, are made from stacked laminated steel sheets. Soft magnetic composite (SMC) materials are based on soft magnetic particles, usually iron-based, with an electrically insulating coating on each particle. SMC parts are obtained by compressing insulating particles using conventional powder metallurgy (PM) compaction processes, possibly with lubricants and / or binders. The use of powder metallurgy techniques allows the manufacture of such parts with greater design freedom than using laminated steel sheets. By using PM, three-dimensional shapes can be obtained by the compaction process, so that the resulting parts are capable of carrying three-dimensional magnetic flux.

[0003] An inductor or reactor is a passive electrical component that can store energy in the form of a magnetic field generated by current passing through the component. An inductor's ability to store energy, inductance (L), is measured in units of henries (H). The simplest inductor is an insulated wire wound as a coil. Current flowing through the turns of the coil generates a magnetic field around the coil whose field strength is proportional to the current and turns / unit of length in the coil. A varying current generates a varying magnetic field, and the varying magnetic field induces a voltage that opposes the change in current that created it. The electromagnetic force (EMF) that opposes the change in current is measured in volts (V) and is related to inductance by Equation 1, v(t)=L di(t) / dt Equation 1 where L is the inductance, t is time, v(t) is the time-varying voltage across the inductor, and i(t) is the time-varying current. That is, an inductor with an inductance of 1 Henry will produce an EMF of 1 volt when the current through it changes at 1 amp / second.

[0004] Ferromagnetic or iron core inductors use a magnetic core made from a ferromagnetic or ferrimagnetic material, such as iron or ferrite, to increase the inductance of the coil. The relatively high magnetic permeability of these core materials and the resulting increase in magnetic field can significantly increase the inductance.

[0005] Two important properties of an SMC part are its magnetic permeability and core loss characteristics. The magnetic permeability μ of a material is a measure of its ability to carry magnetic flux, i.e., its ability to be magnetized. Magnetic permeability is expressed as the induced magnetic flux (B) and is expressed in units of Newtons per Ampere*meter, N / Am, or Volts*seconds / meter. 2 , Vs / m 2 It is defined as the ratio of the magnetic field strength (denoted as H and measured in units of amperes per meter, A / m) to the magnetizing force or magnetic field strength (denoted as H and measured in units of amperes per meter, A / m). Thus, permeability has a magnitude of Volts*Seconds / Amperes*Meter, Vs / Am. Usually, permeability is calculated by dividing the permeability of free space by the magnetic field strength μ0=4*Π*10 -7 Relative permeability μ vs. Vs / Am r =μ / μ0.

[0006] Permeability depends not only on the material carrying the magnetic flux, but also on the applied electric field and its frequency. In technical systems, permeability is often referred to as the maximum relative permeability, which is the maximum relative permeability measured during one cycle of the varying electric field.

[0007] In power electronic systems, inductor cores may be used to filter out undesired signals such as various harmonics. To function efficiently, inductor cores for such applications must have a low maximum relative permeability, which is achieved by having a more linear characteristic of the relative permeability versus the applied electric field, i.e., a stable incremental permeability μ Δ (ΔB=μ Δ *ΔH) and a high saturation flux density. This allows the inductor to operate more efficiently over a wider current range, and the inductor can also be described as having a "good DC bias". The DC bias may be expressed in percentage of the maximum incremental permeability at a particular applied electric field, e.g., 4000 A / m. Furthermore, the low maximum relative permeability and stable incremental permeability combined with the high saturation flux density allows the inductor to carry higher currents, which is particularly beneficial when size is a limiting factor, so that smaller inductors can be used.

[0008] When magnetic materials are exposed to a fluctuating magnetic field, energy losses occur due to both hysteresis losses and eddy current losses. Hysteresis losses are proportional to the frequency of the alternating magnetic field, while eddy current losses are proportional to the square of the frequency. Thus, at high frequencies, eddy current losses are most important, and there is a particular need to reduce eddy current losses while maintaining low levels of hysteresis losses.

[0009] Hysteresis losses (DC losses) are caused by the expenditure of energy required to overcome the magnetic forces held within the iron core components. The forces can be minimized by improving the purity and quality of the base powder and, most importantly, by increasing the temperature and / or time of heat treatment (i.e. stress relief) of the components. Eddy current losses (AC losses) are caused by the generation of electrical currents within the components (bulk eddy currents) and within the soft magnetic particles (in-particle eddy currents) due to changes in magnetic flux caused by alternating current (AC) conditions.

[0010] A high electrical resistivity for the component is desirable to minimize bulk eddy currents. The level of electrical resistivity required to minimize AC losses depends on the type of application (operating frequency) and the size of the component. In addition, the individual powder particles must be coated with a thermally stable electrical insulator, preferably stable above 650°C, to reduce bulk eddy currents while maintaining a low level of hysteresis losses. For applications operating at high frequencies, it is desirable to use powders with relatively fine particle sizes, since the intra-particle eddy currents can be confined to a relatively small volume. Thus, fine powders and high electrical resistivity become even more important for components operating at high frequencies.

[0011] Regardless of how well the grain insulation works, there will always be unlimited bulk eddy currents in the component, causing losses. Bulk eddy current losses are proportional to the cross-sectional area of ​​the constriction carrying the magnetic flux, so components with large cross-sectional areas require relatively high electrical resistivity to limit bulk eddy current losses.

[0012] Insulated iron-based soft magnetic powders (100 mesh powders) having an average particle size of 50 to 150 μm, for example about 80 μm to about 120 μm, with 10 to 30% less than 45 μm, can be used for parts operating at frequencies from 200 Hz up to 10 kHz, whereas parts operating at frequencies from 2 kHz up to 50 kHz are usually based on insulated soft magnetic powders (200 mesh powders) having an average particle size of about 20 to about 75 μm, for example about 30 μm to about 50 μm, with more than 50% less than 45 μm. The average particle size and particle size distribution should preferably be optimized according to the requirements of the application.

[0013] Research into powder metallurgy manufacturing of magnetic core components using coated iron-based powders has been directed toward developing iron powder compositions that enhance certain physical and magnetic properties without adversely affecting other properties of the final component. Desired component properties include, for example, suitable permeability through an extended frequency range, high saturation induction, high mechanical strength, and low core losses, which means that it is desirable to increase the resistivity of the magnetic core.

[0014] Various methods have been used and proposed to search for ways to improve resistivity. One method is based on providing an electrically insulating coating or film on the powder particles before these particles are subjected to compaction. Thus, there are many patent publications teaching various kinds of electrically insulating coatings. Examples of patents published on inorganic coatings are US Pat. No. 6,309,748, US Pat. No. 6,348,265 and US Pat. No. 6,562,458. Coatings of organic materials are known, for example, from US Pat. No. 5,595,609. Coatings containing both inorganic and organic materials are known, for example, from US Pat. No. 6,372,348 and US Pat. No. 5,063,011 as well as from German Patent Publication No. 3,439,397, according to which the particles are surrounded by an iron phosphate layer and a thermoplastic material. European Patent EP1246209B1 describes a ferromagnetic metal-based powder, the surface of which is covered with a coating made of a silicone resin and fine particles of a clay mineral having a layered structure, such as bentonite or talc.

[0015] US Pat. No. 6,756,118 B2 discloses a soft magnetic powder metal composite material comprising at least two oxides encapsulating powder metal particles, the at least two oxides forming at least one common phase.

[0016] Patent application JP2002170707A describes alloyed iron particles coated with a phosphorus-containing layer, the alloying element being silicon, nickel or aluminum. In a second step, the coated powder is mixed with an aqueous solution of sodium silicate and subsequently dried. Powder cores are produced by compacting the powder, and the compacted parts are heat treated at temperatures between 500 and 1000 ° C.

[0017] In JP51-089198 sodium silicate is mentioned as a binder for iron powder particles in producing dust cores by compacting the iron powder and subsequent heat treatment of the compacted part.

[0018] High density usually improves the magnetic properties. In particular, high density is necessary to keep hysteresis losses at a low level and to obtain a high saturation magnetic flux density. Therefore, to obtain high-performance soft magnetic composite parts, it must also be possible to compact the electrically insulating powder composition at high pressure without impairing the electrical insulation, and the part should then be easily ejected from the molding device without impairing the part surface. This in turn means that the ejection force must not be too high.

[0019] Furthermore, to reduce hysteresis losses, stress relief heat treatment of the compression section is necessary, and to obtain effective stress relief, the heat treatment should preferably be carried out in an atmosphere of, for example, nitrogen, argon or air, or in vacuum, at a temperature above 300° C., but below which the insulating coating is not damaged.

[0020] The present invention relates to an iron-based soft magnetic composite powder, the core particles of which are covered with a coating carefully and judiciously selected to give them suitable material properties for compacting the powder to make inductors, optionally and preferably followed by a heat treatment process.

[0021] The present invention was made in view of the need for powder cores primarily intended for use at relatively high frequencies, i.e. frequencies above 2 kHz, in particular 5-100 kHz, where relatively high resistivity and relatively low core losses are essential. Preferably, the saturation flux density should be high enough to allow for miniaturization of the cores. Furthermore, it should be possible to produce cores without the use of die wall lubrication and / or compaction pressures in excess of 1200 MPa to compact the metal powder. Summary of the Invention

[0022] One object of the present invention is to provide a novel iron-based composite powder that can be compressed into soft magnetic components having high resistivity and low core losses, the novel iron-based composite powder being particularly suitable for use in the manufacture of inductor cores for power electronics.

[0023] Another object of the present invention is to provide an iron-based powder composition, including an electrically insulating iron-based powder, that can be compressed into soft magnetic components having high strength, suitable maximum magnetic permeability, and high induction.

[0024] It is a further object of the present invention to provide a means for minimizing hysteresis losses and keeping bulk eddy current losses to a low level without degrading the iron-based powder electrically insulating coating.

[0025] It is yet another object of the present invention to provide iron-based powder compositions, including electrically insulated iron-based powders, that are compacted into soft magnetic components having green strengths high enough to allow for reduced compaction pressures while maintaining good magnetic performance.

[0026] It is a further object of the present invention to provide a method for manufacturing soft magnetic components having high strength, high induction, low core losses, minimizing hysteresis losses while keeping eddy current losses at low levels.

[0027] Another object of the present invention is to provide a method for manufacturing pressed and optionally heat treated soft magnetic iron-based composite inductor cores having low core losses and "good" DC bias in combination with sufficient mechanical strength and acceptable magnetic flux density (induction).

[0028] Another object of the invention is to provide means that make it possible to avoid the use of organic binders, which can cause problems during high temperature heat treatments, for example due to decomposition, and thus to increase the magnetic flux density and reduce the core losses.

[0029] It is a further object of the present invention to provide means for improving the magnetic properties of soft magnetic composite materials, in particular for improving the core losses and / or DC bias.

[0030] The present invention provides an iron-based composite powder that can be used to manufacture, for example, an inductor having a high saturation magnetic flux density and reduced core loss, and can greatly simplify the manufacturing process, and a process method for processing the mixture. Note that the following [1] to

[15] are each an embodiment or aspect of the present invention. [1] A composition comprising particles A and particles B, each of the particles A and B comprising a core, the core of the particle A being a soft magnetic iron-based core, and the core of the particle B being formed from an Fe—Si alloy; The surfaces of the cores of the particles A and B are coated with phosphorus-containing insulating layers A1 and B1, respectively; The particle A having the insulating coating layer A1 is provided with an additional layer A2 on top of the layer A1, the layer A2 being formed from a compound of formula (I) or a reaction product thereof; M(OR 1 ) x (R 2 ) y Formula (I) wherein M is selected from Si, Ti, Al or Zr, preferably Si or Ti, more preferably Si; R 1 is a straight or branched chain alkyl group having up to 4, preferably up to 3, carbon atoms, preferably an ethyl or methyl group; R 2 is an organic group, optionally including a functional group; x+y is OR 1 Groups and R 2 an integer indicating the number of groups, where x is selected from 1, 2, and 3, and y is selected from 1, 2, and 3, with the proviso that (x+y)=4, when M is Si, Zr, or Ti; (x+y)=3, where x is selected from 1 and 2, and y is selected from 1 and 2, if M is Al. A composition wherein said particles A further comprise particles C attached to or incorporated in said layer A2, said particles C being particles of a material having a Mohs hardness of 3.5 or less. [2] the particle B has a layer B2 on the layer B1, the layer B2 being formed from a compound of formula (I) or a reaction product thereof; M(OR 1 ) x (R 2 ) y Formula (I) wherein M is selected from Si, Ti, Al or Zr, preferably Si or Ti, more preferably Si; R 1 is a straight or branched chain alkyl group having up to 4, preferably up to 3, carbon atoms, preferably an ethyl or methyl group; R 2 is an organic group, optionally including a functional group; x+y is OR 1 Groups and R 2 an integer indicating the number of groups, where x is selected from 1, 2, and 3, and y is selected from 1, 2, and 3, with the proviso that (x+y)=4, when M is Si, Zr, or Ti; (x+y)=3, where x is selected from 1 and 2, and y is selected from 1 and 2, if M is Al. Optionally, the particles B contain particles C attached to or incorporated in the layer B2; The composition described in [1]. [3] The composition according to [1], wherein the core particle of the particle A has an apparent density of 3.3 to 3.7 g / ml, preferably 3.3 to 3.6 g / ml, preferably 3.35 to 3.6 g / ml, for example, 3.4 to 3.6 g / ml, 3.35 to 3.55 g / ml, or 3.4 to 3.55 g / ml, and the particle B has an apparent density of 3.0 to 5.5 g / ml, preferably 3.5 to 5.5 g / ml, preferably 4.0 to 5.0 g / ml, for example, 4.3 to 4.8 g / ml. [4] The composition according to any one of [1] to [3], wherein the powder composition further comprises a lubricant. [5] The composition according to any one of [1] to [4], wherein the layers A2 and / or B2 are formed from a compound of formula (I), or the layers A2 and / or B2 are formed from a reaction product of a compound of formula (I), and the number of metal atoms M in one molecule is 2 to 20. [6] R 2 comprises one or more of the following functional groups: amine, diamine, amide, imide, epoxy, mercapto, disulfide, chloroalkyl, hydroxyl, ethylene oxide, ureido, urethane, isocyanato, acrylate, glyceryl acrylate, carboxyl, carbonyl, and aldehyde. [7] The composition of any one of [1] to [6], wherein the compound of formula (I) or a reaction product thereof is an oligomer of the compound of formula (I), said oligomer being selected from alkoxy-terminated amino-silsesquioxanes, amino-siloxanes, oligomeric 3-aminopropyl-alkoxy-silanes, 3-aminopropyl / propyl-alkoxy-silanes, N-aminoethyl-3-aminopropyl-alkoxy-silanes or N-aminoethyl-3-aminopropyl / methyl-alkoxy-silanes or mixtures thereof. [8] The composition according to any one of [1] to [7], wherein the particles C contain bismuth or bismuth(III) oxide. [9] The composition according to any one of [1 to [8], wherein the weight ratio of particles A to B (A:B) is 95:5 to 50:50, preferably 90:10 to 60:40, and most preferably 80:20 to 60:40.

[10] 1. A method for manufacturing a compacted and heat treated part, comprising: a) providing a composition as defined in any one of claims [1] to [9]; b) compressing said composition, optionally mixed with a lubricant, with a uniaxial pressing movement in a die, preferably at a compression pressure of 400-1200 MPa; c) ejecting the compressed part from the die; and d) heat treating the ejected parts in a non-reducing atmosphere at a temperature of up to 800°C.

[11] A part obtainable by compressing a composition as defined in any one of claims [1] to [9] or by the method as defined in

[10] .

[12] The component described in

[11] , which is an inductor core.

[13] 10. An inductor core according to claim 12, having a resistivity ρ of 3,000 μΩm or more, preferably 6,000 μΩm or more or 10,000 μΩm or more; a saturation flux density Bs of 1.1 T or more, preferably 1.2 T or more or 1.3 T or more; an iron loss of 21 W / kg or less at a frequency of 10 kHz and an induction of 0.1 T; a coercive force of 240 A / m or less at 10000 A / m, preferably 230 A / m or less or 220 A / m or less; and a DC bias of 50% or more at 4000 A / m.

[14] [1] to [8], for particles B having a coating layer B1 for improving the magnetic properties, preferably the core loss and / or the DC bias, of a soft magnetic composite material. Use of coated Fe-Si alloy particles.

[15] The use according to

[14] , wherein the Fe-Si particles are coated with layer B1 and layer B2 as defined in [2]. [Brief description of the drawings]

[0031] [Figure 1] FIG. 1 is a pictorial representation of two embodiments of the present invention, where in embodiment 1, particle A has coating layers A1 and A2, and particle B has only coating layer B1, and in embodiment 2, particle B has both coating layers B1 and B2. Note that the particle sizes and coating layer thicknesses of particles A and B may differ, and FIG. 1 may not reflect true scale of the particles and their coatings. [Diagram 2] As obtained in the examples, the DC bias of samples 1 and 3 that can be derived from the change in magnetic permeability at different magnetic field strengths measured at 50 kHz is shown. [Diagram 3] Figure 2 shows the green strength of different compositions of the examples with 0.4 wt% particulate lubricant added, compressed at 1000 MPa, with different die temperatures and different lubricants (top: Lub A, amide wax; bottom: Lub B, composite lubricant according to WO 2010 / 062250). [Figure 4] 1 shows the green strength of different compositions of the examples with 0.4 wt% particulate lubricant added, compressed at 1200 MPa, with different die temperatures and different lubricants (top: Lub A, bottom: Lub B). [Diagram 5] Core losses obtained for parts pressed on a die at 80° C. and with 0.4 wt. % of different particulate lubricants are shown. Top: Low frequency (1 kHz) core loss at 1 T. Bottom: High frequency (20 kHz) core loss at 0.2 T. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0032] In order to achieve at least one of the above objects and / or further objects not mentioned that will emerge from the following description, the present invention provides:

[0033] 1. A composition comprising particles A and particles B, each of which comprises a core, the core of particle A being a soft magnetic iron-based core and the core of particle B being formed from an Fe-Si alloy; The surfaces of the cores of particles A and B are coated with phosphorus-containing insulating layers A1 and B1, respectively; Particle A having an insulating coating layer A1 is provided with an additional layer A2 on top of layer A1, layer A2 being formed from a compound of formula (I) or a reaction product thereof, M(OR1) x (R2) y Formula (I) wherein M is selected from Si, Ti, Al or Zr, preferably Si or Ti, more preferably Si; R1 is a linear or branched alkyl group having up to 4, preferably up to 3, carbon atoms, preferably an ethyl or methyl group; R2 is an organic group optionally containing a functional group; x+y are integers representing the number of OR1 and R2 groups, respectively, and if M is Si, Zr or Ti, x is selected from 1, 2 and 3, and y is selected from 1, 2 and 3, with the proviso that (x+y)=4; (x+y)=3, where x is selected from 1 and 2, and y is selected from 1 and 2, if M is Al. A composition wherein particles A further comprise particles C attached to or incorporated in layer A2, particles C being particles of a material having a Mohs hardness of 3.5 or less.

[0034] 2. The composition according to item 1, wherein the particle B has a layer B2 on a layer B1, and the layer B2 is formed from a compound of formula (I) or a reaction product thereof; M(OR1) x (R2) y Formula (I) wherein M is selected from Si, Ti, Al or Zr, preferably Si or Ti, more preferably Si; R1 is a linear or branched alkyl group having up to 4, preferably up to 3, carbon atoms, preferably an ethyl or methyl group; R2 is an organic group optionally containing a functional group; x+y are integers representing the number of OR1 and R2 groups, respectively, and if M is Si, Zr or Ti, x is selected from 1, 2 and 3, and y is selected from 1, 2 and 3, with the proviso that (x+y)=4; (x+y)=3, where x is selected from 1 and 2, and y is selected from 1 and 2, if M is Al. Optionally, the composition in which particles B contain particles C attached to or embedded in layer B2.

[0035] 3. The composition according to item 1, wherein the core particles of particle A have an apparent density of 3.3 to 3.7 g / ml, preferably 3.3 to 3.6 g / ml, preferably 3.35 to 3.6 g / ml, for example, 3.4 to 3.6 g / ml, 3.35 to 3.55 g / ml or 3.4 to 3.55 g / ml, and particle B has an apparent density of 3.0 to 5.5 g / ml, preferably 3.5 to 5.5 g / ml, preferably 4.0 to 5.0 g / ml, for example, 4.3 to 4.8 g / ml.

[0036] 4. The composition according to any one of claims 1 to 3, wherein the powder composition further comprises a lubricant.

[0037] and / or B2 are formed from a compound of formula (I) or layers A2 and / or B2 are formed from a reaction product of a compound of formula (I), and the number of metal atoms M in one molecule is 2 to 20.

[0038] 6. The composition according to any one of the preceding claims, wherein R2 comprises one or more of the following functional groups: amine, diamine, amide, imide, epoxy, mercapto, disulfide, chloroalkyl, hydroxyl, ethylene oxide, ureido, urethane, isocyanato, acrylate, glyceryl acrylate, carboxyl, carbonyl and aldehyde, with amine and diamine being preferred.

[0039] 7. The composition according to any one of the preceding claims, wherein the compound of formula (I) or a reaction product thereof is an oligomer of the compound of formula (I), the oligomer being selected from an alkoxy-terminated amino-silsesquioxane, an amino-siloxane, an oligomeric 3-aminopropyl-alkoxy-silane, a 3-aminopropyl / propyl-alkoxy-silane, an N-aminoethyl-3-aminopropyl-alkoxy-silane or an N-aminoethyl-3-aminopropyl / methyl-alkoxy-silane or a mixture thereof.

[0040] 8. The composition according to any one of the preceding claims, wherein particles C comprise bismuth or bismuth(III) oxide.

[0041] 9. The composition according to any one of items 1 to 8, wherein the weight ratio of particles A to B (A:B) is 95:5 to 50:50, preferably 90:10 to 60:40, and most preferably 80:20 to 60:40.

[0042] 10. A method for producing a compacted and heat treated part, comprising: a) providing a composition as defined in any one of items 1 to 9, b) compressing the composition, optionally mixed with a lubricant, with a uniaxial pressing movement in a die, preferably at a compression pressure of 400 to 1200 MPa; c) ejecting the compressed part from the die; and d) heat treating the ejected parts in a non-reducing atmosphere at a temperature of up to 800°C.

[0043] 11. A part obtainable by compressing the composition defined in any one of items 1 to 9 or by the method according to item 10.

[0044] 12. The component according to item 11, which is an inductor core.

[0045] 13. The inductor core according to item 12, having a resistivity ρ of 3,000 μΩm or more, preferably 6,000 μΩm or more or 10,000 μΩm or more; a saturation magnetic flux density Bs of 1.1 T or more, preferably 1.2 T or more or 1.3 T or more; an iron loss of 21 W / kg or less at a frequency of 10 kHz and an induction of 0.1 T; a coercive force of 200 A / m or less, preferably 190 A / m or less or 160 A / m or less; and a DC bias of 50% or more at 4,000 A / m.

[0046] 14. Use of coated Fe-Si alloy particles for particles B with a coating layer B1 as specified above for improving the magnetic properties, preferably core losses and / or DC bias, of a soft magnetic composite material.

[0047] 15. The use according to item 14, wherein the Fe-Si particles are coated with layer B1 and layer B2 as defined in item 2.

[0048] Further embodiments and aspects of the present invention will become apparent from the following detailed description.

[0049] definition In the present invention, unless otherwise indicated, all physical parameters are at room temperature (20° C.) and atmospheric pressure (10 5 It is measured in Pa.

[0050] As used herein, the indefinite article "a" denotes one and more than one and does not necessarily limit the referenced noun to the singular.

[0051] The term "about" means that the amount or value in question may be the particular value specified or some other value nearby, generally within ±5% of the indicated value. Thus, for example, the phrase "about 100" indicates a range of 100±5.

[0052] The term "and / or" means that all or only one of the listed elements is present. For example, "a and / or b" means "only a," or "only b," or "a and b together." In the case of "only a," the term also covers the possibility that b is not present, i.e., "only a and not b."

[0053] The term "comprising" as used herein is intended to be non-exclusive and non-limiting. Thus, a composition containing a particular component may contain other components than those listed. However, the term also includes the more restrictive meanings of "consisting of" and "consisting essentially of." The term "consisting essentially of" allows for the presence of 10% by weight or less, preferably 5% or less, of materials other than those listed for each composition, and may be completely absent of other materials.

[0054] Whenever a measurable parameter is referred to, the method used in the examples is used. In addition, particle size and particle size distribution can be determined by laser diffraction using standard methods in the art, such as those specified in ISO 13320-1:1999. Particle size can also be classified by dry sieving in accordance with ISO 1497:1983. Resistivity can be determined by four-point probe measurements, as described by Smits, FM, “Measurements of Sheet Resistivity with the Four-Point Probe” BSTJ, 37, p. 371 (1958). In case of discrepancies, the method used in the examples of the present invention takes precedence.

[0055] All documents referenced herein are incorporated by reference in their entirety.

[0056] Detailed Description of the Invention In a first aspect, the present invention provides a method for producing a composition comprising the steps of: i) particles A each comprising an iron-based core and two or more coating layers surrounding the core, the two or more coating layers being provided on the surface of the core and including a first coating layer A1 which is a phosphorus-based insulating coating layer and a second layer A2 provided on the first coating layer A1 and described below; and ii) particles B each comprising a core made of an alloy containing Fe and Si or consisting essentially of Fe and Si, the surface of the FeSi core being provided with at least a phosphorus-based insulating layer B1 and, optionally, a second layer B2 provided on layer B1 and described below; The present invention relates to a composition comprising, consisting essentially of, or consisting of:

[0057] Particles A and B differ from each other at least in terms of the nature of the composition of the core. Thus, the soft magnetic core of particle A is not an alloy containing Fe and Si as specified below for particle B.

[0058] The core of particle A preferably has an apparent density (AD) increased by 7-25% by a milling, grinding or other process that physically alters the irregular surface. The AD of particle A measured according to ISO 3923-1 should be in the range of 3.2-3.7 g / ml, preferably 3.3-3.7 g / ml, preferably 3.3-3.6 g / ml, more preferably greater than 3.3 g / ml to 3.6 g / ml, preferably 3.35-3.6 g / ml, or 3.4-3.6 g / m, or 3.35-3.55 g / ml, or 3.4-3.55 g / ml.

[0059] In another embodiment, the powder composition may include a lubricant.

[0060] The invention further relates to a process for the preparation of a soft magnetic composite material, which comprises compressing, preferably uniaxially, the composition according to the invention in a die, preferably at a compression pressure of 400-1200 MPa, more preferably 600-1200 MPa, and optionally preheating the die to a temperature below the melting temperature of the added lubricant, if a lubricant is present, discharging the obtained green body, and optionally heat treating the green body. The composite part according to the invention preferably has a phosphorus content (P) of 0.01-0.1% by weight, a content of added M (preferably Si) of 0.02-0.12% by weight, and a content of Bi, added in the form of a metal or semi-metal particulate compound C, of ​​0.05-0.35% by weight.

[0061] Each component of the invention will now be described in further detail, without wishing to limit the invention to the specific embodiments described.

[0062] Core of particle A The iron-based core particles of particle A can be of any origin, such as water atomized, gas atomized or originating from sponge iron powder. Water atomized particles are preferred.

[0063] The iron-based soft magnetic core may be selected from the group consisting essentially of pure iron, meaning that the iron content is 90% by weight or more, preferably 95% by weight or more, more preferably 99% by weight or more. The remainder may be any material or element other than Si. Particularly preferably, the core consists of iron and unavoidable impurities. These may be present in an amount of up to 0.1% by weight.

[0064] Core of particle B The core of particle B is made of an iron alloy containing iron and silicon (Si), and the core is preferably gas atomized. In addition to iron and silicon, other alloying metals may be present, but to a lesser extent than Si. Fe constitutes 80% by weight or more, more preferably 90% by weight or more, of the alloy forming the core of particle B.

[0065] The balance is formed by unavoidable impurities and other alloying metals, including at least Si. Si forms at least 1 wt.% or the alloy forming the core of particle B, preferably 2.5 wt.% or more, even more preferably 4 wt.% or more. The upper limit of Si is 15 wt.% or less, but typically 10 wt.% or less of Si is present. Preferably, the upper limit of the amount of Si is 9 wt.% or less or 8 wt.% or less, but may be 7% or less. The amount of unavoidable impurities and other elements other than Fe and Si is typically 10 wt.% or less, more preferably 5 wt.% or less, even more preferably 2 wt.% or less. It may also be as low as 1.0 or 0.1 wt.%, with the balance being Fe and Si. Such other alloying elements may include Al, Ni, Co, or combinations thereof.

[0066] In one embodiment, the core of particle B is made of an Fe-Si alloy consisting of 90% by weight or more Fe and 10% by weight or less Si and unavoidable impurities in an amount of 0.2% by weight or less, preferably 0.1% by weight or less. In a preferred aspect of this embodiment, the amount of Si is 4.0-7.0% by weight, the balance being formed by Fe and unavoidable impurities in an amount of 0.2% by weight or less, for example 0.1% by weight or less.

[0067] Shape of particles A and B It has now also surprisingly been found that the electrical resistivity of the pressed and heat treated parts according to the invention can be further improved when particles with a smooth particle surface are used as the core of particle A. Such a preferred morphology is manifested, for example, by an increase in the apparent density of the iron or iron-based powder of more than 7% or more than 10%, or more than 12% or more than 13%, resulting in an apparent density of 3.2 to 3.7 g / ml, preferably more than 3.3 g / ml and up to 3.6 g / ml, preferably 3.4 to 3.6 g / ml, or 3.35 to 3.55 g / ml.

[0068] Such powders with the desired apparent density may be obtained from a gas atomization process or water atomized powder. When water atomized powders are used, they are preferably subjected to a grinding, milling or other process, which physically changes the irregular surface of the water atomized powder. If the apparent density of the powder increases too much, beyond about 25% or 20%, it means that the total core loss increases, for water atomized iron-based powders above about 3.7 or about 3.6 g / ml.

[0069] It has also been found that the shape of the core particles, for example, affects the resistivity results. The use of irregular particles results in lower apparent density and resistivity than a less uniform and more smooth particle shape. Therefore, according to the present invention, particles that are nodular, i.e. rounded and irregular, or spherical or nearly spherical, are preferred. For components operating at high frequencies, where powders with relatively fine particle sizes (such as 100 and 200 mesh) are preferably used, high resistivity becomes even more important, so "high AD" becomes even more important for these powders.

[0070] Amount of particles The composition of the present invention contains particles A and B together with their respective coating layers. The total amount of particles A and B (including their coating layers) relative to the total weight of the composition is preferably 85% by weight or more, more preferably 90% by weight or more, even more preferably 95% by weight or more, for example 98% by weight or more, and may be up to 100% by weight.

[0071] The amount of particles B including their coating layers is preferably 5-50% by weight, more preferably 10-40% by weight, based on the total weight of particles A and B (i.e., [B] / [B+A]×100=5-50, preferably 10-40). It may also be 20-40% by weight. The weight ratio of the particles is preferably 95:5-50:50, preferably 90:10-60:40, most preferably 80:20-60:40, and is expressed as [A]:[B].

[0072] In addition to the particles A and B including their coating layers, the composition may optionally further contain additives such as lubricants.

[0073] The amount of lubricant is preferably less than 1 wt%, more preferably less than 0.7 wt%, or most preferably less than 0.5 wt%, based on the total weight of the composition.

[0074] Particle core size The particle size of particles A and B is not limited and is determined by the intended use of the manufactured part, but the median particle size (by weight), Dw50, of the core of particles A and B is 250 microns or less, more preferably 75 microns or less, for example 45 microns or less.

[0075] First Coating Layer (Inorganic) A1 / B1 Each of the cores forming the particles A and B is provided with a first inorganic insulating layer A1 and B1, respectively. Methods for forming such coatings are described, for example, in WO 2009 / 116 938 A1.

[0076] Layers A1 and B1 are phosphorus-based, which means that they contain P in an amount of at least 5 atomic %, preferably at least 8 atomic % or more, more preferably 10 atomic % or more, expressed as element P and determined by conventional methods such as ESCA or XPS. The phosphorus is preferably present in the form of phosphates, diphosphates or polyphosphates, in which case the cations are preferably selected from protons, alkali metals and earth alkali metals, preferably protons, sodium and potassium.

[0077] This first coating layer A1 / B1 may be obtained by treating the respective core particles with phosphoric acid dissolved either in water or in an organic solvent. In the aqueous solvent, rust inhibitors and surfactants are optionally added. A preferred method for coating iron-based powder particles is described in US Pat. No. 6,348,265. The treatment may be carried out once, but may also be repeated. The phosphorus-based coating layer A1 / B1 preferably does not contain additives such as dopants, rust inhibitors or surfactants. The coating A1 / B1 is an insulating coating. Optionally, the coating may be neutralized by treatment with a suitable base.

[0078] The amount of phosphor in layers A1 and B1 may be 0.01 to 0.15% by weight of the total composition.

[0079] Second Coating Layer A2 / B2 The layer A2 located on the first phosphorus-based inorganic insulating layer A1 of the particle A is a layer formed by a compound of the following general formula (I) or a reaction product thereof: As used herein, the term "reaction product" means a product obtained by reaction of one molecule of a compound of formula (I) with another molecule of a compound of formula (I) and / or with the layer A1 or B1, examples of the reaction product include partial or total condensates thereof. M(OR1) x (R2) y Formula (I)

[0080] In formula (I), M is selected from Si, Ti, Al or Zr, preferably Si or Ti, more preferably Si, and R1 is an alkyl group having up to 4, preferably up to 3 carbon atoms, more preferably an ethyl group -C2H5 or a methyl group -CH3.

[0081] R2 is an organic group optionally containing a functional group, preferably R2 contains 1 to 14, more preferably 1 to 8 carbon atoms, even more preferably 1 to 6 carbon atoms, for example 1 to 3 carbon atoms. The R2 group may be linear, branched, cyclic or aromatic, and is preferably a linear or branched alkyl group.

[0082] In one embodiment, any functional group of R2 is present and is preferably selected from the group containing one or more heteroatoms selected from the group consisting of N, O, S, P and halogen atoms, with N, O, S and P being preferred. Examples of such groups include amine, diamine, amide, imide, epoxy, mercapto, disulfide, chloroalkyl, hydroxyl, ethylene oxide, ureido, urethane, isocyanato, acrylate, glyceryl acrylate, carboxyl, carbonyl and aldehyde.

[0083] Additionally, x+y are integers that represent the number of OR1 and R2, respectively, selected to satisfy the valence of M. When M is Si, Zr, or Ti, (x+y)=4, and when M is Al, (x+y)=3. If M is Si, Zr or Ti, x is selected from 1, 2 and 3 and y is selected from 1, 2 and 3, with the proviso that (x+y)=4, whereas if M is Al, x is selected from 1 and 2 and y is selected from 1 and 2, with the proviso that (x+y)=3.

[0084] Hereinafter, this layer is called layer A2. In one embodiment, layer A2 is formed only on particle A having insulating layer A1, but not on particle B having coating layer B1 ("embodiment 1"). In another embodiment (also called "embodiment 2"), a layer formed by a compound of general formula (I) or its reaction products, such as its partial or total condensates, optionally together with particle C, is also present on layer B1 of particle B, in which case this layer is called layer B2 (see FIG. 1). Thus, the description and definition of layer B2 are the same as those of layer A2, and in such a case, particles A and B are distinguished by their different cores. Layers A2 and B2 may be formed simultaneously from the same compound by treating a mixture of particle A having layer A1 and particle B having layer B1 with a compound of formula (I)), but they may be formed separately by using different compounds of formula (I) or their reaction products to form layers A2 and B2, respectively.

[0085] Layer A2 and optional layer B2 may be formed from a compound of formula (I) and a particle C, but may also be formed, at least in part, by a (poly)condensation reaction product of formula (I), thereby encapsulating particle C. For example, if the compound of formula (I) is trimethoxyaminopropylsilane, the layer may be formed by its (poly)condensation product formed under the formation of an alcohol (in this case methanol). Such a reaction product preferably contains 2 to 50, more preferably 2 to 20 atoms M in one molecule. In such a (poly)condensation reaction, the OR1 group is eliminated by releasing HOR1, leaving a MOM bond (2 atoms M in the (poly)condensation product). In the case of 3 M atoms in the polycondensation product, for example, a MOMOM bond is formed. Here, each M still has an R2 group present in the starting material.

[0086] When M is Si, Ti or Zr and x=2 and y=2, a linear molecule with multiple MOM bonds is formed, such as MOMOMOM. The R2 groups remain, so the compound can be represented by (H or R1)OM(R2)2-O-(MR2)2-O-(MR2)2-. When M is Si, Ti or Zr and x=3 and y=1, a three-dimensional polysiloxane network is formed, with each M still having one group R2.

[0087] In each case, the groups R1 and R2 may be different from each other. Furthermore, when both particles A and B contain respective layers A2 and B2, the layers may be formed from the same compound of formula (I) or its reaction products, or from different compounds of formula (I) or its reaction products.

[0088] Trace amounts of water or another agent capable of initiating or catalyzing a condensation reaction may be beneficial so that a condensation product can be formed. Such water may be present, for example, on the particles on which the coating layers A2 and optionally B2 are formed in the presence of physisorbed water present on the phosphorus-containing coating A1 or B1. Additionally, the phosphorus-containing layers A1 and B1 typically contain PO4, which may be fully or partially neutralized by protons. 3 - groups. Without wishing to be bound by theory, it is believed that these groups can initiate a reaction, such as reacting with the compound of formula (I) to form a POM bond. For example, the P-OH group in the phosphorus-containing layer A1 or B1 can react with the group OR1 by eliminating HO-R1 and forming a POM bond, thereby anchoring layer A2 (and B2, if present) to layer A1 or B2, respectively. Additional information regarding the formation of coating layers A2 and B2 can be found in WO 2009 / 116938 A1, which is incorporated herein by reference in its entirety.

[0089] In one embodiment, the compound of formula (I) is selected from trialkoxysilanes and dialkoxysilanes, titanates, aluminates or zirconates. In one embodiment, layers A2 and / or B2 comprise an oligomer of a compound of formula (I) selected from alkoxy-terminated alkyl / alkoxy oligomers of silanes, titanates, aluminates or zirconates. Herein, the central atom (preferably Si) preferably contains an amine group as a substituent on the alkyl group (i.e., R2 is an alkylamine).

[0090] As shown above, both particles A and B have a first coating layer A1 and B1, respectively. Particle A further has a second coating layer A2 provided on layer A1. Particle B optionally has a second coating layer B2 provided on layer B1.

[0091] In one embodiment, both particles A and B have coating layers A2 and B2, respectively, whereas in another embodiment, only particle A has coating layer A2. In this case, particle B, which does not have coating layer B2, has insulating layer B1 as its outermost layer. Otherwise, layers A2 (and B2, if present) are typically the outermost layers of particles A and B, and particle C is incorporated into or attached to layers A2 and optionally B2.

[0092] The compounds of formula (I) may also be selected from derivatives, intermediates or oligomers of silanes, siloxanes and silsesquioxanes (M is Si), or the corresponding titanates, aluminates or zirconates (M is Ti, Al and Zr, respectively), or mixtures thereof.

[0093] According to one embodiment, the layers A2 and optionally B2 are formed by compounds of formula (I). The layers thus contain compounds of formula (I) and / or their reaction products with the underlying phosphorus-based insulating layer A1 / B1.

[0094] According to another embodiment, layers A2 and / or B2 contain a reaction product of a compound of formula (I) itself, i.e. a reaction product of one molecule of a compound of formula (I) with another molecule of a compound of formula (I), where the number M of metal atoms per molecule of the reaction product is 2 or more, preferably 5 or more, and 50 or less, preferably 20 or less. This reaction product is a polycondensate of two or more compounds of formula (I), which may be the same or different from one another.

[0095] In one embodiment, the layers A2 and / or B2 may have a homogeneous composition, meaning that the entire layer is formed, for example, from the compound of formula (I) or by its polymer. In another embodiment, the layers A2 and / or B2 may be formed by two or more sublayers having different compositions. For example, the layers A2 and / or B2 may comprise two or more sublayers. Herein, the layer directly on the insulating phosphorus-based insulating layer may be formed only by the compound of formula (I), while an additional sublayer on top of this layer may be formed from an oligomer or polymer of the compound of formula (I). The weight ratio of the sublayer containing the compound of formula (I) to the layer of its oligomer or polymer may be any value, but is preferably 1:0 to 1:2, more preferably 2:1 to 1:2.

[0096] When more than one compound of formula (I) or reaction product thereof is present, the chemical functionality thereof need not be the same.

[0097] The compound of formula (I) is in one embodiment selected from the group of trialkoxysilanes and dialkoxysilanes, titanates, aluminates or zirconates, examples of which include 3-aminopropyl-trimethoxysilane, 3-aminopropyl-triethoxysilane, 3-aminopropyl-methyl-diethoxysilane, N-aminoethyl-3-aminopropyl-trimethoxysilane, N-aminoethyl-3-aminopropyl-methyl-dimethoxysilane, 1,7-bis(triethoxysilyl)-4-azaheptane, triaminofunctional propyl-trimethoxysilane, 3-ureidopropyl-triethoxysilane, 3-isocyanatopropyl-triethoxysilane, tris(3-trimethoxysilylpropyl)-isocyanurate, 0-(propargyloxy)-N-(triethoxysilylpropyl)-urethane, 1-aminomethyl-triethoxysilane, 1-aminoethyl-methyl-dimethoxysilane or mixtures thereof. These types of compounds may be commercially available from companies such as Evonik Ind., Wacker Chemie AG, Dow Corning, Mitsubishi Int. Corp., and Famas Technology Sari.

[0098] The oligomer or polymer of the compound of formula (I) may be selected from alkoxy-terminated alkyl-alkoxy-oligomers of silanes, titanates, aluminates or zirconates.The oligomer may thus be selected from methoxy, ethoxy or acetoxy-terminated amino-silsesquioxanes, amino-siloxanes, oligomeric 3-aminopropyl-methoxy-silanes, 3-aminopropyl / propyl-alkoxy-silanes, N-aminoethyl-3-aminopropyl-alkoxy-silanes or N-aminoethyl-3-aminopropyl / methyl-alkoxy-silanes or mixtures thereof.

[0099] The total amount of layers A2 and, if present, B2 is not particularly limited, but may be, for example, 0.05 to 0.8% by weight, or 0.05 to 0.6% by weight, or 0.1 to 0.5% by weight, or 0.2 to 0.4% by weight, or 0.3 to 0.5% by weight of the total composition.

[0100] Any of the above embodiments include the addition of particles C made of a metal or metalloid or a compound thereof having a Mohs hardness of 3.5 or less, preferably 3.0 or less. The particles C preferably have a weight median particle size D of 5 μm or less, more preferably 3 μm or less, most preferably 1 μm or less. w 50. The Mohs hardness of the metal or semi-metallic particulate compounds is preferably 3.0 or less, more preferably 2.5 or less. SiO2, Al2O3, MgO and TiO2 are not included in the present invention because they are abrasive and have a Mohs hardness much greater than 3.5. Abrasive compositions, even nano-sized particles, can cause irreversible damage to the electrical insulating coating, resulting in poor ejection and deterioration of the magnetic and / or mechanical properties of the heat-treated parts.

[0101] Examples of materials for the particles C include the following groups: lead-based, indium-based, bismuth-based, selenium-based, boron-based, molybdenum-based, manganese-based, tungsten-based, vanadium-based, antimony-based, tin-based, zinc-based, cerium-based compounds and one or more thereof may be used. Each metal itself may also be used.

[0102] The particles C may be made of oxides, hydroxides, hydrates, carbonates, phosphates, fluorspars, sulfides, sulfates, sulfites, acid chlorides or mixtures thereof of the abovementioned metals. According to a preferred embodiment, the particles C are made of bismuth or bismuth(III) oxide.

[0103] Other examples of particles C include alkali or alkaline earth metals and their salts, such as carbonates. Preferred examples include calcium, strontium, barium, lithium, potassium or sodium carbonates.

[0104] The metal or metalloid or compound thereof as particles C is present in the composite material in an amount of up to 0.8% by weight of the composition, for example, 0.05 to 0.6% by weight, more preferably 0.1 to 0.5% by weight, or most preferably 0.15 to 0.4% by weight.

[0105] Particle C is attached to or incorporated in at least one of the outermost layers, i.e. layers A2 and / or B2, of particles A and / or B. In one embodiment, only the outermost layer of particle A contains, is incorporated into, or is attached to particle C. In another embodiment, both particles A and B contain, are incorporated into, or are attached to particle C.

[0106] The particles C are made of a metal or metalloid, including, for example, boron, including compounds (such as salts) of the respective metals or metalloids, and alloys of the metals or metalloids.

[0107] In contrast to many applications and proposed methods where low core losses are desired, a particular advantage of the present invention is that no organic binder needs to be used in the powder composition, which is subsequently compacted in a compaction step. The heat treatment of the green compact can therefore be carried out at a relatively high temperature without the risk of the organic binder decomposing. The relatively high heat treatment temperature also improves the magnetic flux density and reduces the core losses. Improved temperature stability is also achieved, since the absence of organic material in the final heat treated core allows the core to be used in high temperature environments without the risk of loss of strength due to softening and decomposition of the organic binder.

[0108] Nevertheless, in one or more of the above embodiments, a particulate lubricant may be added to the composition. The particulate lubricant may facilitate compression without the need to apply die wall lubrication. The particulate lubricant may be selected from the group consisting of primary and secondary fatty acid amides, transamides (bisamides) or fatty acid alcohols. The lubricating portion of the particulate lubricant may be a saturated or unsaturated chain containing 12 to 22 carbon atoms. The particulate lubricant may preferably be selected from stearamide, erucamide, stearyl-erucamide, erucyl-stearamide, behenyl alcohol, erucyl alcohol, ethylene-bisstearamide (i.e., EBS or amide wax). A preferred lubricant is a particulate composite lubricant comprising a core containing 10-60 wt. % of at least one primary fatty acid amide having more than 18 and up to 24 carbon atoms, and 40-90 wt. % of at least one bis-amide, said lubricant particles also comprising at least one metal oxide nanoparticle attached to the core. Examples of such particulate composite lubricants are disclosed in WO 2010 / 062250, which is incorporated herein by reference in its entirety, and in an embodiment the lubricants disclosed therein are used in the present invention. The preferred lubricants of this document are also preferred lubricants in the present invention.

[0109] The particulate lubricant may be present in an amount of 0.1 to 0.6%, or 0.2 to 0.4%, or 0.3 to 0.5%, or 0.2 to 0.6% by weight of the composition.

[0110] Preparation process of the composition The process for preparing the composition according to the invention comprises coating soft magnetic iron-based core particles and Fe-Si particles, each preferably produced and treated to obtain an apparent density of 3.2-3.7 g / ml, with a phosphorus-based compound to obtain phosphorus-based insulating layers A1 and B1, leaving the surfaces of the core particles A and B electrically insulated. The coatings A1 and B1 can be formed on a mixture of the iron-based and Fe-Si core particles or can be formed separately on the core particles.

[0111] The coated core particles A with layer A1 and optionally particles B with layer B1 are then mixed with a) a compound of formula (I) or its reaction product and particles C with a Mohs hardness of less than 3.5 as described above to form coating layers A2 and optionally B2. When a mixture of particles A with layer A1 and particles B with layer B1 is used, layers A2 and B2 are formed on each particle. When it is desired to form a layer from the compound of formula (I) only on particles A with layer A1, the formation of layer A2 is carried out before the mixing of the particles. Needless to say, it is also possible to provide layers A2 and B2 separately before mixing, and thus form coating layers A2 and B2 with different compositions.

[0112] The process optionally further comprises mixing the obtained particles or a mixture thereof with a lubricant as defined above.

[0113] Manufacturing process for soft magnetic parts The manufacturing process of the soft magnetic composite according to the invention comprises uniaxially compressing the composition according to the invention in a die at a compression pressure of at least 600 MPa, preferably more than 1000 MPa but not more than 1200 MPa, optionally preheating the die to a temperature below the melting temperature of the optionally added lubricant, optionally preheating the powder to 25-100°C before compression, discharging the resulting green body, and optionally heat treating the green body. Herein, the peak temperature should be below 800°C to avoid decomposition or damage of the particle coating layer, preferably below 750°C.

[0114] The heat treatment process can be in a vacuum, a non-reducing, inert atmosphere (such as nitrogen or argon), or a weakly oxidizing atmosphere, for example, 0.01-3% by volume oxygen. In some cases, the heat treatment is performed in an inert atmosphere followed by a quick exposure to an oxidizing atmosphere. The temperature can be up to 800°C, but is preferably below 750°C or even below 700°C.

[0115] At the heat treatment conditions, the lubricant, if used, should be evaporated as completely as possible. This is usually achieved at temperatures above about 150-500 ° C, preferably above about 250-500 ° C, during the first part of the heat treatment cycle. At higher temperatures, compound C (metallic or semi-metallic parts) may react with the compound of formula (I) and partially form a network. This may further improve the mechanical strength and electrical resistivity of the part. At the highest temperatures (preferably in the range of 550-750 ° C, more preferably 600-750 ° C, even more preferably 630-700 ° C, for example 630-670 ° C), the compact may reach a complete stress release where the coercivity of the composite and thus the hysteresis losses are minimized.

[0116] The compressed and heat-treated soft magnetic composite material produced according to the present invention preferably has a phosphorus content of 0.01-0.15% by weight of the component, a content of M (preferably Si) added to the base powder of 0.02-0.12% by weight of the component, and if Bi is added in the form of metal or semi-metallic particles as particles C with a Mohs hardness of less than 3.5, the content of Bi can be 0.05-0.35% by weight of the component.

[0117] The obtained magnetic core may be characterized by low total losses of less than about 41 W / kg at a frequency of 20 kHz and an induction of 0.1 T, in the frequency range of 2-100 kHz, typically 5-100 kHz. Furthermore, the resistivity ρ is greater than 2000, preferably greater than 4000, most preferably greater than 6000 μΩm, and the saturation flux density Bs is greater than 1.1, preferably greater than 1.2, most preferably greater than 1.3 T. Furthermore, the coercivity at 10000 A / m should be less than 240 A / m, preferably less than 230 A / m, most preferably less than 200 A / m, and the DC bias should be greater than or equal to 50% at 4000 A / m.

[0118] example The examples are intended to illustrate particular embodiments and should not be construed as limiting the scope of the invention.Unless otherwise specified, the magnetic performance and material strength of the components were evaluated in the following manner.

[0119] Samples for magnetic evaluation were pressed into toroids with an inner diameter of 45 mm, an outer diameter of 55 mm and a height of 5 mm, and for material strength evaluation, TRS bars were pressed according to SS-EN ISO 3325:2000. During pressing, the tooling die was optionally preheated to 80°C. The pressed parts were heat treated in a two-step sequence with an initial activation step held at 430°C for 30 minutes, followed by a relaxation step held at 675°C for 25 minutes. Both steps were performed in nitrogen with a small amount of oxygen (2500-7500 ppm O2, preferably the amount was 5000 ppm O2).

[0120] For induction, B and coercivity measurements, the rings were "wired" with 100 turns for the primary circuit and 100 turns for the secondary circuit, allowing the measurement of the magnetic properties with a hysteresisgraph, Brockhaus MPG 200 (1T; DC and low frequency iron losses measured from 50 to 1000Hz). For high frequency iron loss measurements, the rings were "wired" with 100 turns for the primary circuit and 20 turns for the secondary circuit, then measured with a Laboratorio Elettrofisico Engineering srl, AMH-200 device (0.05, 0.1 and 0.2T; measured from 2 to 50kHz). Green TRS were measured according to SS-EN-23995.

[0121] Example 1 Example 1 Pure water atomized iron powder with iron content over 99.5 wt% and average particle size of about 45 μm. The powder was then treated with a phosphorus-containing solution according to WO 2008 / 069749. A coating solution was prepared by dissolving 30 ml of 85 wt% phosphoric acid in 1000 ml of acetone, then 30 ml to 60 ml of acetone solution was used per 1000 grams of powder. After mixing the phosphoric acid solution with the metal powder, the mixture is dried. Optionally, the powder was mixed a second time with 10 ml to 40 ml of acetone solution and then dried.

[0122] The coated powder was then further mixed by stirring with 0.25 wt% aminoalkyl-trialkoxysilane (Dynasylan® Ameo) followed by 0.15 wt% oligomer of aminoalkyl / alkyl-alkoxysilane (Dynasylan® 1146), both manufactured by Evonik Ind, to form particle A with layer A1 and an additional layer formed by two sublayers. The composition was further mixed with 0.3 wt% fine powder of bismuth (III) oxide as particle C to finally form layer A2. This treated powder is called Aa and is an example of particle A.

[0123] Gas atomized Fe-Si (containing 6.5 wt% Si) was treated separately with a phosphorus-containing solution to form particles B with layer B1 according to WO 2008 / 069749. A coating solution was prepared by dissolving 30 ml of 85% weight phosphoric acid in 1000 ml of acetone, then 10 ml to 40 ml of acetone solution was used per 1000 grams of powder. After mixing the phosphoric acid solution with the metal powder, the mixture is dried. The powder was mixed a second time with 10 ml to 40 ml of acetone solution and then dried. This powder is called Ba and is an example of powder B.

[0124] Two powders containing particles Aa and Ba were then used as samples 1, 2 and 3, where sample 1 was 100% Aa, sample 2 was 100% Ba only, and sample 3 was a mixture of 70% Aa and 30% Ba by weight. Each of samples 1, 2 and 3 was mixed with particulate lubricant Lubr1 (amide wax) before compression. The amount of lubricant used was 0.4% by weight of the composition.

[0125] Example 2 All samples from Example 1 were compressed at 1000 MPa using a tool die preheated to 80° C., and the compacts were then heat treated as described above. [Table 1]

[0126] As seen in Table 1, the mixture of particles A and B has a lower coercivity and therefore less loss. Sample 3 has resistivity >10000; μmax 210; B@10kA / m (1.33T); Core loss @1T 100Hz (8.5W / kg); Core loss @0.1T 10kHz (16W / kg); and Core loss @0.1T 20kHz (33W / kg). However, the pure gas atomized Fe-Si powder (sample 2) cannot be compressed at such a low compaction pressure. The mechanical strength of sample 2 is too weak and breaks when the sample is ejected from the compaction tool (die).

[0127] As can be seen in FIG. 2, the DC bias of the material measured at 4000 A / m and 50 kHz is improved by 10% by adding 30 wt % Ba to Aa.

[0128] Example 3 - Increasing Green Intensity Powders containing coated particles Aa and Ba obtained as described in Example 1 were mixed in the range of 10-50% by weight of Ba in Aa. Each of these mixtures was then mixed with particulate lubricant Lub A (amide wax) or Lub B (composite lubricant according to WO 2010 / 062250) before compaction. The amount of lubricant used was 0.4% by weight of the composition.

[0129] Each composition was then pressed at 1000 and 1200 MPa with die temperatures of 60, 80° C. and room temperature for the mixtures containing Lub A, and 60, 80 and 100° C. for the mixtures containing Lub B. The pressed parts were then heat treated and evaluated as described above.

[0130] The addition of Lubr2 significantly improves the green strength of the compacted parts, as can be seen in Figures 3 and 4. The mechanical strength obtained using Lubr1 as lubricant makes it possible to process materials containing as high as 50 wt.% Ba at moderate compaction pressures (1000-1200 MPa).

[0131] Example 4 - Optimal amount of FeSi in the mixture Powders containing coated particles A and B obtained as described in Example 1 were mixed in the range of 10-50% by weight of Ba in Aa. Each of these mixtures was then mixed with particulate lubricant Lub A or Lub B prior to compression. The amount of lubricant used was 0.4% by weight of the composition.

[0132] Each composition was then compressed at 800, 1000 and 1200 MPa with a die temperature of 80° C. The compressed parts were then heat treated and evaluated as described above.

[0133] As can be seen in Figure 5, the addition of Ba to Aa initially improves the core loss, especially at low frequencies. However, it is clear that the optimum composition is reached at about 40 wt. % Ba addition. With even higher Ba additions, the reduction in core loss compared to pure Aa is almost completely lost.

[0134] Example 5 This example shows the advantage of using gas atomized Fe-Si compared to an equivalent amount of water atomized Fe-Si powder.

[0135] An Fe-Si powder similar to that of Example 1, with the only difference being that the powder was produced by water atomization, was processed according to the process described in Example 1. This powder was designated Ca.

[0136] 70% Aa and 30% Ca were mixed to produce sample 4. Sample 4 was further mixed with 0.4% Lubr1 before compression.

[0137] The resulting samples were compressed, heat treated and tested according to Example 2.

[0138] Table 2 below shows the results obtained from testing of Sample 4 compared to the results obtained for Sample 1. [Table 2]

[0139] Table 2 shows that some improvement in green strength was recorded for sample 4 compared to sample 3. However, coercivity @ 10 kA / m and core loss @ 0.1 T and 10 kHz deteriorated.

Claims

1. A composition comprising particles A and particles B, each of said particles A and B comprising a core, said core of said particle A being a soft magnetic iron-based core and said core of said particle B being formed from an Fe—Si alloy; The total amount of particles A and B relative to the total weight of the composition is 85% by weight or more; the surfaces of the cores of the particles A and B are coated with phosphorus-containing insulating layers A1 and B1, respectively; The particle A having the phosphorus-containing insulating layer A1 has an additional layer A2 on top of the layer A1, the layer A2 being formed from a compound of formula (I) or a reaction product thereof; M(OR 1 )(R x )(R 2 )(R y Formula (I) wherein M is selected from Si, Ti, Al or Zr; R 1 is a straight or branched chain alkyl group having 4 or fewer carbon atoms; R 2 is an organic group, optionally including a functional group; x and y are OR 1 Groups and R 2 an integer representing the number of groups, where x is selected from 1, 2, and 3, and y is selected from 1, 2, and 3, if M is Si, Zr, or Ti, with the proviso that (x+y)=4; When M is Al, x is selected from 1 and 2, and y is selected from 1 and 2, with the proviso that (x+y)=3. the particles A further include particles C attached to or incorporated in the layer A2, the particles C being particles of a material having a Mohs hardness of 3.5 or less; A composition in which the amount of inevitable impurities and elements other than Fe and Si in the core of particle B is 2 wt % or less based on the weight of the core of particle B.

2. The particle B has a layer B2 on the layer B1, the layer B2 being formed from a compound of formula (I) or a reaction product thereof; M(OR 1 )( x (R 2 )) y Formula (I) wherein M is selected from Si, Ti, Al or Zr; R 1 is a straight or branched chain alkyl group having 4 or fewer carbon atoms; R 2 is an organic group, optionally including a functional group; x + y are OR 1 Groups and R 2 an integer representing the number of groups, where x is selected from 1, 2, and 3, and y is selected from 1, 2, and 3, if M is Si, Zr, or Ti, with the proviso that (x+y)=4; When M is Al, x is selected from 1 and 2, and y is selected from 1 and 2, with the proviso that (x+y)=3. Optionally, said particles B contain particles C attached to or incorporated in said layer B2; The composition of claim 1.

3. 2. The composition of claim 1, wherein the core of said particle A has an apparent density of 3.3 to 3.7 g / ml and the core of said particle B has an apparent density of 3.0 to 5.5 g / ml.

4. 2. The composition of claim 1, wherein the core of said particles A has an apparent density of 3.3 to 3.6 g / ml and the core of said particles B has an apparent density of 3.5 to 5.5 g / ml.

5. 2. The composition of claim 1, wherein the core of said particle A has an apparent density of 3.35 to 3.6 g / ml and the core of said particle B has an apparent density of 4.0 to 5.0 g / ml.

6. 2. The composition of claim 1, wherein the core of said particle A has an apparent density of 3.4 to 3.6 g / ml and the core of said particle B has an apparent density of 4.3 to 4.8 g / ml.

7. 7. The composition according to claim 3, wherein the core of said particles A has an apparent density of 3.35 to 3.55 g / ml.

8. The composition according to any one of claims 3 to 6, wherein the core of said particles A has an apparent density of 3.4 to 3.55 g / ml.

9. The composition of claim 1 , further comprising a lubricant.

10. The composition according to any one of claims 1 to 9, wherein the layers A2 and / or B2 are formed from a compound of formula (I) or the layers A2 and / or B2 are formed from a reaction product of a compound of formula (I), and the number of metal atoms M in one molecule is 2 to 20.

11. R 2 11. The composition of any one of claims 1 to 10, wherein said copolymer comprises one or more of the following functional groups: amine, diamine, amide, imide, epoxy, mercapto, disulfide, chloroalkyl, hydroxyl, ethylene oxide, ureido, urethane, isocyanato, acrylate, glyceryl acrylate, carboxyl, carbonyl, and aldehyde.

12. 12. The composition of any one of claims 1 to 11, wherein the compound of formula (I) or reaction product thereof is an oligomer of the compound of formula (I), said oligomer being selected from alkoxy terminated amino-silsesquioxanes, amino-siloxanes, oligomeric 3-aminopropyl-alkoxy-silanes, 3-aminopropyl / propyl-alkoxy-silanes, N-aminoethyl-3-aminopropyl-alkoxy-silanes or N-aminoethyl-3-aminopropyl / methyl-alkoxy-silanes or mixtures thereof.

13. 13. The composition of claim 1, wherein the particles C comprise bismuth or bismuth(III) oxide.

14. The composition according to any one of claims 1 to 13, wherein the weight ratio of particles A to B (A:B) is from 95:5 to 50:

50.

15. 1. A method for manufacturing a compacted and heat treated part, comprising: a) providing a composition as defined in any one of claims 1 to 14, b) compressing the composition in a uniaxial press motion in a die at a compression pressure of 400-1200 MPa; and c) ejecting said compressed part from said die.

16. A part obtainable by compressing a composition as defined in any one of claims 1 to 14 or by the method as defined in claim 15.

17. 17. The component of claim 16, which is an inductor core.

18. 18. The inductor core of claim 17 having a resistivity ρ of 3,000 μΩm or more; a saturation magnetic flux density Bs of 1.1 T or more; an iron loss of 21 W / kg or less at a frequency of 10 kHz and an induction of 0.1 T; a coercivity of 240 A / m or less at 10,000 A / m; and a DC bias of 50% or more at 4,000 A / m.

19. A method for improving the magnetic properties of a soft magnetic composite material, comprising using a composition according to any one of claims 1 to 13.

20. 20. The use according to claim 19, wherein said particles B are coated with layers B1 and B2 as defined in claim 2.

Citation Information

Patent Citations

  • Soft magnetic material, manufacturing method thereof, powder magnetic core, and manufacturing method thereof

    JP2007088156A

  • Powder for metallurgy, powder magnetic core, method for producing powder for metallurgy and method for producing powder magnetic core

    JP2010126786A

  • Composite soft magnetic material and method for producing the same

    JP2010185126A

  • Powder for dust core and dust core, and method of manufacturing the same

    JP2010251600A

  • Magnetic material

    JP2011187634A